The graphic designer's guide to portfolio design - Myers, Debbie Rose (J. Wiley & Sons, 2014)
Landing a job in graphic design or multimedia starts with the creation of a portfolio that showcases a student's best work. With sample portfolios, interviews with leaders in graphic design and advertising industries, and step-by-step instruction for creating professional print and digital portfolios, this book helps students successfully transition from design student to design professional. Now fully updated, it is the only guide to creating job-winning print-based and digital portfolios specifically for graphic designers.